2021
DOI: 10.3233/thc-218013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of masticatory exercise on cognitive function in community-dwelling older adults

Abstract: BACKGROUND: Mastication improves cognitive function by activating cerebral cortical activity, and it is important to demonstrate the cognitive effects of masticatory training using a variety of different interventions. OBJECTIVE: This study aimed to evaluate the effects of masticatory exercise on cognitive function in healthy older adults living in the community. METHODS: For six weeks, twelve participants performed a masticatory exercise using a NOSICK exerciser device, and thirteen subjects performed daily l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Further research is required to understand better the relationship between ageing, body composition and neuromuscular control of masticatory muscles in PWID. Additionally, studies should explore the potential impact of masticatory muscle training, either alone or combined with physical activity exercise, on overall health and well-being, including cognitive function (Chuhuaicura et al 2019;Lin et al 2020;Kim 2021;Yang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to understand better the relationship between ageing, body composition and neuromuscular control of masticatory muscles in PWID. Additionally, studies should explore the potential impact of masticatory muscle training, either alone or combined with physical activity exercise, on overall health and well-being, including cognitive function (Chuhuaicura et al 2019;Lin et al 2020;Kim 2021;Yang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches show positive findings. The effects on cognitive function with masticatory exercise intervention exhibit promising results 63 , 64 , 65 , 66 , 67 Jaw-tapping, a form of masticatory exercise, for four weeks improves memory function in cognitively impaired patients. 63 The oral rehabilitation of four edentulous patients, in the case of converting from removable dentures to implant-retained dentures, resulted in improved working memory and oral health quality of life.…”
Section: Brain-stomatognathic Axismentioning
confidence: 99%
“… 64 Evidence suggests that masticatory function has a positive influence on cognitive function. 51 , 60 , 63 , 64 , 65 , 66 , 67 …”
Section: Brain-stomatognathic Axismentioning
confidence: 99%
“…While it is not clear whether poor oral health predicts dementia, substantial data suggests that oral health declines as cognitive impairment and dementia progresses [ 7 , 12 , 14 , 15 , 16 ]. Furthermore, it has been demonstrated that masticatory exercise improves cognitive function in older adults [ 17 ] and thus the link between cognitive decline and masticatory dysfunction is now clear [ 8 , 18 , 19 , 20 , 21 , 22 ]. As loss of masticatory activity [ 8 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 ] and sedentary life style [ 23 , 24 ] are risk factors for age-related cognitive decline, there is a need to focus attention on those sub-populations that experience greater oral health deterioration or impairment of the stomatognathic system, and those having living sedentary lives.…”
Section: Introductionmentioning
confidence: 99%